2020
DOI: 10.1098/rstb.2019.0645
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid bioconversion in harpacticoid copepods in a changing environment: a transcriptomic approach

Abstract: By 2100, global warming is predicted to significantly reduce the capacity of marine primary producers for long-chain polyunsaturated fatty acid (LC-PUFA) synthesis. Primary consumers such as harpacticoid copepods (Crustacea) might mitigate the resulting adverse effects on the food web by increased LC-PUFA bioconversion. Here, we present a high-quality de novo transcriptome assembly of the copepod Platychelipus littoralis , exposed to changes in both temperature (+3°C) and dietary LC-PUF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 61 publications
(93 reference statements)
0
25
0
Order By: Relevance
“…Copepods, one of the most abundant groups within zooplankton, contain high levels of n-3 LC-PUFA, particularly EPA and DHA [21,55], prompting interest to elucidate to which extent biosynthesis, along diet can contribute to the abundance of these essential nutrients. While several studies provided evidence suggesting that some copepod species can indeed produce LC-PUFA endogenously, the potential contribution of microbial endosymbionts for such metabolic ability could not be completely ruled out [31][32][33]. In the present study, we addressed this methodological drawback by performing a comprehensive retrieval for all genes encoding desaturase and elongase enzymes with potential roles in the PUFA and LC-PUFA biosynthesis in a representative species within Harpacticoida, T. californicus.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Copepods, one of the most abundant groups within zooplankton, contain high levels of n-3 LC-PUFA, particularly EPA and DHA [21,55], prompting interest to elucidate to which extent biosynthesis, along diet can contribute to the abundance of these essential nutrients. While several studies provided evidence suggesting that some copepod species can indeed produce LC-PUFA endogenously, the potential contribution of microbial endosymbionts for such metabolic ability could not be completely ruled out [31][32][33]. In the present study, we addressed this methodological drawback by performing a comprehensive retrieval for all genes encoding desaturase and elongase enzymes with potential roles in the PUFA and LC-PUFA biosynthesis in a representative species within Harpacticoida, T. californicus.…”
Section: Discussionmentioning
confidence: 97%
“…Early studies using 14 C-labelled fatty acids suggested some copepods showed the ability to bioconvert PUFA into LC-PUFA [23,24]. Studies involving feeding trials using LC-PUFA-deficient diets or stable isotope labelled fatty acids provided further evidence that Harpacticoida and Cyclopoida copepods possess some capacity to produce n-3 LC-PUFA endogenously [25][26][27][28][29][30][31][32][33]. However, these studies could not unequivocally establish that the abovementioned metabolic activities observed were indeed due to the copepod's enzymatic complement, and hence it is difficult to completely rule out that LC-PUFA are rather synthesized by microbes that coexist within the copepod.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of high-quality transcriptomes, especially for copepods, is still limited, although, in recent years, there has been an increase in molecular resources for metazoan zooplankton [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In this study, we present the first molecular resource for an eucalanoid copepod, Rhincalanus gigas .…”
Section: Discussionmentioning
confidence: 99%
“…With primary consumers, it is relatively easy to provide fresh, single species of phytoplankton or macroalgae as foods that are likely representative of nature since many short-lived primary consumers feed on temporally limited algal blooms. In this special issue, numerous authors employed this approach and focused on feeding pure algal diets [20,21,29,30,33,34]; with their springtail experiments Kühn et al [35, this issue] were also able to offer mixed dried diets of bacteria, microalgae, fungi and plants. At intermediate trophic levels, it can be difficult to meet the nutritional requirements of consumers by feeding single species, particularly for longer-duration experiments, since such predators are rarely so specialized [28,31].…”
Section: (A) Matching Composition Of Experimental and Natural Dietsmentioning
confidence: 99%